2011
DOI: 10.1044/1058-0360(2011/10-0019)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Length, Complexity, and Grammatical Correctness on Stuttering in Spanish-Speaking Preschool Children

Abstract: Purpose: To explore the effects of utterance length, syntactic complexity, and grammatical correctness on stuttering in the spontaneous speech of young, monolingual Spanishspeaking children. Method: Spontaneous speech samples of 11 monolingual Spanish-speaking children who stuttered, ages 35 to 70 months, were examined. Mean number of syllables, total number of clauses, utterance complexity (i.e., containing no clauses, simple clauses, or subordinate and /or conjoined clauses), and grammatical correctness (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
(87 reference statements)
1
16
2
1
Order By: Relevance
“…By comparison, in English, the speaker needs to be concerned only about definiteness (i.e., "a" vs. "the"). Thus, the production of more speech disfluencies in Spanish than in English may be related to the fact that Spanish has more grammatical and syntactic restrictions Watson, Byrd, & Carlo, 2011).…”
Section: Influence Of Language Producedmentioning
confidence: 99%
“…By comparison, in English, the speaker needs to be concerned only about definiteness (i.e., "a" vs. "the"). Thus, the production of more speech disfluencies in Spanish than in English may be related to the fact that Spanish has more grammatical and syntactic restrictions Watson, Byrd, & Carlo, 2011).…”
Section: Influence Of Language Producedmentioning
confidence: 99%
“…We selected syllables as opposed to words given the morphosyntactic structure of Spanish (Watson et al, 2011). The trained bilingual research assistant counted syllables for each sample in English and Spanish by hand following the guidelines used by Watson et al (2011).…”
Section: Syllablesmentioning
confidence: 99%
“…If after consulting the first author the output could not be definitively understood the utterance was marked as unintelligible. Similar to Watson et al (2011), syllables were then coded for type and number of disfluencies.…”
Section: Syllablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to examine growth, rather than skills at onset, is underscored by the fact that children's lexical and syntactic skills are rapidly developing during the time that stuttering has its typical onset, between 2;6 and 3;6 years;months (Bloodstein, 2006). Historically, numerous studies have noted that stuttering is exacerbated during the production of syntactically demanding utterances (e.g., Bauerly & Gottwald, 2009;Bernstein Ratner, 1998;Gaines, Runyan, & Meyers, 1991;Watson, Byrd, & Carlo, 2011). Kinematic studies of the effects of syntactic complexity on fluent speech movement variability have reported that young CWS often cannot even comply with experimental tasks to fluently produce enough trials of longer, more complex utterances (MacPherson & Smith, 2013).…”
Section: Language Growth As a Predictor Of Recovery Statusmentioning
confidence: 99%